“CHALLENGES IN TEACHING GRAMMAR AND VOCABULARY TO A1 LEVEL LEARNERS IN UZBEK SCHOOLS” - Abdullayeva Nigora Shavkatovna; Ro'ziyeva Nilufar Adkhamjon qizi (Лучшие интеллектуальные исследования, 2023)
Abstract: This articlediscusses the challenges in teaching grammar and vocabulary to A1 level learners. A1 level learners are beginners in learning a language, and they have limited knowledge of grammar rules and vocabulary. The main challenges in teaching these learners include their lack of exposure to the language, their unfamiliarity with the target language's grammar structure, and their limited vocabulary.